Pre-Training Muscle Characteristics of Subjects Who Are Obese Determine How Well Exercise Training Will Improve Their Insulin Responsiveness. Issue 3 (March 2017) - Stuart, Charles A.; Lee, Michelle L.; South, Mark A.; Howell, Mary E.A.; Cartwright, Brian M.; Ramsey, Michael W.; Stone, Michael H.
Abstract : Abstract: Stuart, CA, Lee, ML, South, MA, Howell, MEA, Cartwright, BM, Ramsey, MW, and Stone, MH. Pre-training muscle characteristics of subjects who are obese determine how well exercise training will improve their insulin responsiveness. J Strength Cond Res 31(3): 798–808, 2017—Only half of prediabetic subjects who are obese who underwent exercise training without weight loss increased their insulin responsiveness. We hypothesized that those who improved their insulin responsiveness might have pretraining characteristics favoring a positive response to exercise training. Thirty nondiabetic subjects who were obese volunteered for 8 weeks of either strength training or endurance training. During training, subjects increased their caloric intake to prevent weight loss. Insulin responsiveness by euglycemic clamps and muscle fiber composition, and expression of muscle key biochemical pathways were quantified. Positive responders initially had 52% higher intermediate muscle fibers (fiber type IIa) with 27% lower slow-twitch fibers (type I) and 23% lower expression of muscle insulin receptors. Whether after weight training or stationary bike training, positive responders' fiber type shifted away from type I and type IIa fibers to an increased proportion of type IIx fibers (fast twitch). Muscle insulin receptor expression and glucose transporter type 4 (GLUT4) expression increased in all trained subjects, but these moderate changes did not consistently translate to improvement in whole-body insulin responsiveness. Exercise training of previously sedentary subjects who are obese can result in muscle remodeling and increased expression of key elements of the insulin pathway, but in the absence of weight loss, insulin sensitivity improvement was modest and limited to about half of the participants. Our data suggest rather than responders being more fit, they may have been less fit, only catching up to the other half of subjects who are obese whose insulin responsiveness did not increase beyond their pretraining baseline.